COMPLIANCE OF HYPERTENSION PATIENTS IN DOING SELF-CARE: A GROUNDED THEORY STUDY - Pius A. L. Berek; Yati Afiyanti (Jurnal Sahabat Keperawatan, 2020)
Hypertensi as a one of non-communicable diseases is need of serious attention and dealt with " nation-wide " given the high prevalence and usually people do not realize that he was suffering from hypertension. Generally only known when they come for treatment to the health service because of illness or other complaints, so hypertension is often known as " the silent killer ". Patient compliance in undergoing hypertension treatment is also a determinant that affects the control of patient's blood pressure . The most important main determinant The effect on adherence to take antihypertensive medication is long suffered from hypertension. This study aims to develop theoretical concepts about strategies to improve patient compliance in self-care for hypertensive patients both pharmacologically and non-pharmacologically. The study design using qualitatively with five participants and purposive sampling. From the results of the study, six themes were obtained : experience of adherence to control, experience of handling symptoms and complications, experience of taking medication adherence, experience of adherence to managing diets, lack of adherence to exercise, and obstacles to adherence . It is recommended that hypertensive patients can improve compliance for routine antihypertensive drug consumption by making simple schedules and enhancing their self-concept.